القيمة الإنذارية لانقلاب موجة [T] عقب احتشاء العضلة القلبية الحاد المسرب له ستربتوكيناز - بله, حسام; جحجاح, أكرم; غازي, حسام (Latakia University Journal -Medical Sciences Series, 2019)
شملت هذه الدراسة (92) مريضاً باحتشاء عضلة قلبية حاد، في مشفى الأسد الجامعي باللاذقية في الفترة الواقعة بين 20/1/2003-20/1/2004. قسم المرضى في البداية لمجموعتين: (C) تحوي (42) مريض (45.7%) لم يتلقوا العلاج الحال للخثار. (S) تحوي (50) مريض (54.3%) تلقوا العلاج الحال للخثار. وقد تم متابعة التبدلات التخطيطية لموجة [T] في المجموعة (S) لمدة (8) أيام كما تم متابعة كل المرضى لمدة شهر كامل. وهكذا صنفنا مرضى المجموعة (S) إلى قسمين: 1- مجموعة Negative T (N.T) تحوي (43) مريض (86%) وهم المرضى الذين امتكلوا موجات T سالبة في مساري تزحل قطعة S-T نحو الأعلى. 2- مجموعة Positive T (P.T) تحوي (7) مرضى (14%) وهم المرضى الذين امتكلوا موجات T موجبة في مساري تزحل قطعة S-T للأعلى. لقد أظهرت المتابعة لمدة شهر للمرضى أهمية استعمال الستربتوكيناز حيث أنها حسنت البقيا بمعدل (44%). وقللت الاختلاطات الخاصة باحتشاء العضلة القلبية الحاد [الصدمة القلبية بمعدل (47%) وقصور القلب السريري بمعدل (53%) ولم يقلل هذا العلاج من نكس الاحتشاء ومعاودة الألم الخناقي]. وعندما قارنا المجموعة (N.T) مع المجموعة (P.T) وجدنا أن مرضى المجموعة (N.T) امتلكوا وظيفة بطينية أفضل (%55 < EF بنسبة 53.5% مقابل 0%)، حيوية جيدة للعضلة القلبية (62.5% لـ N.T )، انفتاح أعلى للشريان الإكليلي المحتشي (TIMI = 2®3 بنسبة 73% مقابل 0%)، وترافق أعلى مع مشعرات عودة التروية (83.7% مقابل 28.6%) وأخيراً تحسن البقيا لثلاثين يوماً (92%). This study included (92) patients of acute myocardial infraction (AMI) in AL-Assad University Hospital in Lattakia, between 20/1/2003-20/1/2004. First, they were divided into two groups: C- Group included (42) patients (45.7%) who has not received thrombolytic therapy. S- Group included (50) patients (54.3%) who has received thrombolytic therapy. We followed up ECG changes of (T) waves in (S) group for (8) days and followed up all patients for (30) days. So we divided patients of S-group into two categories: 1- Negative [T} group (N.T) included (43) patients (86%) who have negative [T] waves in leads of S-T elevation. 2- Positive [T] group (P.T) included (7) patients (14%) who have positive or flate T waves in leads of S-T elevation. The follow up of patients for one month showed the importance of using streptokinase. It improved survival rates for (44%) and made complications rate of (AMI) lower incidence, for cardiac shock rate (47%) and clinical heart failure rate (53%) but did not make relapse infarction and frequency of angina lower incidence. And when we had compared (N.T) group with (P.T) group we found that patients of (N.T) group had better ventricular function (EF > 55% for 53.5% vs 0%). Good viable of myocardium [62.5% for (N.T) group] – more patency of infarcted related artery (TIMI = 2®3) (73% vs 0%). More accompany with markers of reperfusion (83.7% vs 28%) and higher 30 day survival rates (92%).